The AAPRISS Platform: Learning and Taking Action to Reduce Social Inequalities in Health to help PHIR. (13th November 2019) - Lang, T; Marquis, C; Haschar-Noé, N; Kelly-Irving, M; Huot-Royer, M; Grosclaude, P; Delpierre, C
Abstract: : Today, the reduction of social inequalities in health is on the political agenda in public health. The complex reality of the determinants of these health inequalities remains difficult to understand and translate into practical actions. One of the reasons is that the circulation of expertise amongst researchers, actors in the field, and public decision is not systematic and still too rare. In 2013, the Federative Institute of Interdisciplinary Research and Studies Health Society (IFERISS) of Toulouse has an interdisciplinary platform (health, the humanities, and the social sciences) that directly offers expertise to public health actors, institutions, and local communities in order to respond to public health issues. At the request of the actors, AAPRISS can intervene at all stages of a study or an intervention, from conceptual and methodological construction to implementation support, and data analysis and use. In particular, the team has expertise in public policy evaluation, support for transferability according to the key functions/implementation/context (FIC) model, and awareness-raising at the intersection of urban planning and health. The platform is in a multi-year partnership with local authorities, the regional health agency of Occitanie, the primary health insurance funds of Occitanie, and various partners in civil society. Six years after the establishment of the AAPRISS platform, there is a strong demand for support and research from the actors and institutions. However, funding for activities remains uncertain despite the support of the National Cancer League and an increasingly strong network of partners. Mixed structures housing spaces for both research and action, which create a dynamic of Population Health Intervention Research, are showing themselves to be effective and seem to meet a need, but their financial stability is insufficient to sustain their activities and promote sustainable reduction of social inequalities in health. Key messages: Mixed structures housing spaces for both research and action, which create a dynamic of Population Health Intervention Research, are showing themselves to be effective and seem to meet a need. But the financial stability of this mixed structures is insufficient to sustain their activities and promote sustainable reduction of social inequalities in health.